Fatty acids, Sterols and Antioxidant compounds of minor and neglected cultivar of Sicilian virgin olive oils - Mineo, V.; Planeta, D.; Finoli, C.; Giuliano, S. (Progress in Nutrition, 2007)
Acidic and sterol composition, pigment fraction and antioxidant compounds (tocopherols, total phenols and polar phenols) from eight monovarietal Sicilian olive oil samples, analyzed during the crop seasons from 2003/2004 to 2005/2006, are reported. Cultivars were divided, according to their diffusion, in main, minor and neglected cultivars. Encouraging data were observed for minor and neglected cultivars, for some revaluation in regard to their relevance, because they showed the highest content in tocopherols, in total phenols and polar phenols compared with main cultivars.